MicroRNA-155-5p suppresses the migration and invasion of lung adenocarcinoma A549 cells by targeting Smad2 - Lin, Jianfeng (Oncol Lett, 2018)
Lung cancer is one of the major causes of cancer-related deaths worldwide. Notably, miR-155-5p is one of the most amplified miRNAs in non-small cell lung carcinoma (NSCLC). However, the role of miR-155-5p in lung cancer metastasis has not been fully evaluated. In the present study, miR-155-5p mimic and inhibitor were used to investigate the effects of miR-155-5p on the metastasis of human lung carcinoma A549 cells. The study indicated that transfection of miR-155-5p mimic significantly suppressed cell proliferation, migration and invasion of A549 cells, whereas its inhibition significantly promoted cell proliferation, migration and invasion of A549 cells, suggesting a potential therapeutic application of miR-155-5p in controlling lung cancer metastasis. Moreover, transfection of miR-155-5p mimic suppressed the expression of Smad2/3, ZEB1, ZEB2 and N-cadherin and induced that of E-cadherin, whereas its inhibition significantly upregulated the expression of Smad2/3, ZEB1, ZEB2 and N-cadherin and downregulated that of E-cadherin. Collectively, the findings suggest that miR-155-5p suppresses the proliferation, migration and invasion of A549 cells. Therefore, loss of miR-155-5p may serve an essential role in tumorigenesis and tumour progression in lung cancers.